(untitled) (Revista de Investigaciones Universidad del Quindío, 2018)
New titanium complexes of general formula Ti(OAR)4•HOR with different withdrawing group (Cl, CN, NO2) were synthesized by alcohol-phenol exchange method and were characterized by proton nuclear magnetic resonance (1H NMR) that gave evidence of the formation of dimeric structures with octahedrally coordinated Ti centers. In addition, by thermogravimetric analysis (TGA) that registered loss of volatile and allowed to adjust the experimental molecular weight of each pre-catalyst. Through chemical analysis by atomic absorption was determined elemental percentage of aluminum in the triethylaluminum co-catalyst.